2020
DOI: 10.1152/ajpendo.00042.2020
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxysteroid (17β) dehydrogenase 12 is essential for metabolic homeostasis in adult mice

Abstract: Hydroxysteroid 17-beta dehydrogenase 12 (HSD17B12) is suggested to be involved in the elongation of very long chain fatty acids. Previously, we have shown a pivotal role for the enzyme during mouse development. In the present study we generated a conditional Hsd17b12 knockout (HSD17B12cKO) mouse model by breeding mice homozygous for a floxed Hsd17b12 allele with mice expressing the tamoxifen-inducible Cre recombinase at the ROSA26 locus. Gene inactivation was induced by administering tamoxifen to adult mice. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 74 publications
1
12
0
Order By: Relevance
“…Its gene, termed HSD17B12, was also knocked out in our screen. Lipidomics analysis of blood serum of a mouse KO showed accumulation of several sphingolipid classes with shorter than 18-carbon fatty acid side chains, in line with the proposed role for HSD17B12 in fatty acid elongation 62 . HSD17B12 has been reported to have specificity for C-18, C-20, and C-22 carbon atoms length 63 , 64 .…”
Section: Discussionsupporting
confidence: 72%
“…Its gene, termed HSD17B12, was also knocked out in our screen. Lipidomics analysis of blood serum of a mouse KO showed accumulation of several sphingolipid classes with shorter than 18-carbon fatty acid side chains, in line with the proposed role for HSD17B12 in fatty acid elongation 62 . HSD17B12 has been reported to have specificity for C-18, C-20, and C-22 carbon atoms length 63 , 64 .…”
Section: Discussionsupporting
confidence: 72%
“…This would allow us to saturate cellular exposure to lipid intermediates and avoid the possibility of bacteria processing the intermediates prior to digestion by C. elegans animals. Similar to let-767 in C. elegans , the 3-ketoacyl reductase in mice, HSD17B12, was found to be essential for development in mice and knockout of the gene in adult mice resulted in reduced body weight, reduced lipid content, and caused liver toxicity hypothesized to be from accumulation of toxic intermediates [46], [47]. 3-ketoacyl reductases perform the second step in fatty acid synthesis/elongation, metabolizing 3-oxoacyl-CoA to 3-hydroxyacyl-CoA (Fig.5A) [48].…”
Section: Resultsmentioning
confidence: 99%
“…Under extreme circumstances, haploinsufficiency of the HSD17B12 gene in female mice resulted in subfertility. HSD17B12 can affect fatty acid elongation and ceramide accumulation in the serum ( 38 ). Previous data showed that central ceramides participate in the timing of female puberty ( 39 ), suggesting that HSD17B12 could be a candidate gene for female puberty.…”
Section: Discussionmentioning
confidence: 99%